أنظمة الأجور وأثرها على أداء العاملين في مؤسسات وشركات القطاع العام الصناعي في سوريا " دراسة ميدانية على شركات الغزل والنسيج في الساحل السوري " - ميا, علي; زيود, لطيف; ناصر, سومر اديب (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يركز البحث بشكل أساسي على دراسة واقع أجور الأفراد العاملين في القطاع العام الصناعي السوري من خلال دراسةٍ علمية ومنهجية, وتقديم المقترحات اللازمة لتطوير وتحديث سياسة الأجور الحالية المتبعة في القطاع العام, وخصوصاً بعد تزايد الفجوة بين الأسعار والأجور الحالية من جهة, وتزايد عدد الأفراد الذين يعملون في هذا القطاع من جهةٍ أخرى, حيث أصبحت الأجور في القطاع العام أحد أسباب مشاكل الإدارة في سوريا باعتراف معظم المسؤولين وأصحاب القرار, وفي هذا الإطار يتناول البحث مفهوم الأجور وأهميتها, والأسس التي يتم الاعتماد عليها في تحديد وحساب أجور الأفراد العاملين في القطاع العام, إضافةً إلى كيفية تحديد هيكل الأجور بشكلٍ علمي ابتداءً من تقييم الوظائف والأعمال وانتهاءً بتحديد هيكل الأجور النهائي المناسب. كما يركّز البحث على دراسة الأداء الفردي والعوامل المؤثرة به, ويتناول البحث أيضاً العلاقة بين الأجور وأداء الأفراد في قطاع الغزل والنسيج, إضافةً إلى دراسة تقييم الأداء الذي يمكننا من معرفة مستويات الأداء الحالية وبالتالي نقاط القوة والضعف في الأداء تمهيداً لرفع مستويات الأداء الحالية وتحسينها. This study focuses on the status of the wages of industrial public sector employees by means of a case study, aiming at putting forward necessary suggestions for a modernization policy of current wages in the public sector. This is especially required, because of the widening gap between prices and salaries, on the one hand, and increase in the number of that sector's workforce, on the other. Even government officials and decision makers acknowledge that public sector wages have become one of the major problems for administration in Syria. In this respect, the study addresses the concept of wages and their importance as well as the criteria upon which wages are determined and calculated. Moreover, the study tries to identify the pay scale scientifically, starting with assessment of positions and jobs, and ending with identification of the final appropriate wages. Furthermore, the study analyzes individual performance and the factors affecting it, including the relationship between wages and performance of employees of textiles and spinning sector. The study finally assesses performance to enable us to know current performance levels, so that points of weakness and strengths can be identified as a way to raise and improve current levels of performance.